2015
DOI: 10.15448/1980-8623.2015.4.20802
|View full text |Cite
|
Sign up to set email alerts
|

Depressão Pós-Parto Materna: Crenças, Práticas de Cuidado e Estimulação de Bebês no Primeiro Ano de Vida

Abstract: Após o nascimento a interação do recém-nascido com o mundo é facilitada pela mãe. Estudos indicam que mães deprimidas podem interagir pouco com seu bebê, gerando déficits comportamentais e cognitivos ao longo do desenvolvimento. Desta forma este estudo pretendeu descrever e relacionar o índice de depressão pós-parto apresentado por mães de bebês e as práticas e crenças sobre cuidado primário e estimulação. Foi utilizada a "Escala de Edinburgh de Depressão Pós-Parto-EPDS" e a "Escala de crenças parentais e prát… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1
19

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 21 publications
1
4
1
19
Order By: Relevance
“…The use of the Edinburgh scale showed that 23.91% of the interviewed mothers showed score ≥ 12, indicating depressive symptomatology. This result is consistent with the values identified in the national literature in similar contexts (22)(23) .…”
Section: Discussionsupporting
confidence: 93%
“…The use of the Edinburgh scale showed that 23.91% of the interviewed mothers showed score ≥ 12, indicating depressive symptomatology. This result is consistent with the values identified in the national literature in similar contexts (22)(23) .…”
Section: Discussionsupporting
confidence: 93%
“…A etiologia da DPP é multifatorial, podendo afetar profundamente o estabelecimento de vínculo afetivo entre mãe e filho, interferindo na qualidade de laços emocionais futuros. Há evidências de prejuízo no desenvolvimento social, emocional e cognitivo da criança, quando a mãe torna-se deprimida 6,14,15,16 .…”
Section: Resultsunclassified
“…(12) In another study performed in Bauru, in the interior of São Paulo, the cutoff point was 12 and the prevalence was 29.5%. (27) Faisal-Cury et al found a prevalence of 15.9%, with data being collected on the tenth day postpartum and adopting the Beck Depression Inventory as a measure of depression. (28) The two surveys closest to the present study found higher prevalence rates: in a public hospital in the city of São Paulo, applying EPDS on the second or third day postpartum and adopting the same cutoff point (≥10), the prevalence was 18%.…”
Section: Discussionmentioning
confidence: 99%